2022
DOI: 10.1177/21582440221134608
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Genre Analysis of Covert Advertising Through Short-Videos in Douyin: The Chinese Version of Tik-Tok

Abstract: Short-video social media is becoming a major advertising tool in the digital age. Covert advertising is increasingly used as a major strategy to effectively promote a product. This study aims to explore the genre of covert short-video advertisements launched in Douyin—the Chinese version of TikTok. It integrates Bhatia’s critical genre analysis approach with Kress and van Leeuwen’s Multimodal Discourse Analysis approach as the conceptual framework. The researchers selected 100 covert short-video advertisements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…The advent of Douyin has promoted the green advertising strategies, which has been widely accepted by customers. Therefore, the green advertising on Douyin is a natural driving force for consumers to purchase goods on this platform, while attracted and influenced by the various green advertisements [6]. From this point, it demonstrates that digital advertising dominates on Douyin and it has attracted a number of people to use this platform to buy goods and products in their everyday life.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The advent of Douyin has promoted the green advertising strategies, which has been widely accepted by customers. Therefore, the green advertising on Douyin is a natural driving force for consumers to purchase goods on this platform, while attracted and influenced by the various green advertisements [6]. From this point, it demonstrates that digital advertising dominates on Douyin and it has attracted a number of people to use this platform to buy goods and products in their everyday life.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Short-video social media is becoming a major advertising tool in the digital age [3]. The analysis of factors influencing consumers' willingness to buy is carried out through cognitive mediation and affective cognitive theories [4].…”
Section: Factors Affecting Consumers' Willingness To Buymentioning
confidence: 99%
“…This study aims to explore the genre of covert short video social media is becoming a major advertising tool in the digital age. Covert advertising is increasingly being used as a major strategy to effectively promote products [7,8]. Li and Xia found that social interaction attributes and media richness have a positive impact on ad effectiveness, including the number of likes, comments, caption length, music category, plot-based implantation methods, multi-character interactions, and male interactions.…”
Section: Literature Reviewmentioning
confidence: 99%